Los tangos de Orfeo de Alberto Rodríguez Muñoz y su deuda con el mito clásico - Bravo de Laguna Romero, Francisco José (Latin American Theatre Review, 2003)
The aim of this study is to present the structures, topics and resources taken from the Greek dramatic tradition by the Argentine playwright Alberto Rodríguez Muñoz in Los tangos de Orfeo. (FJBLR, in Spanish)